Pelatihan dan Sertifikasi Level 2 Teknisi Roda 4 Suzuki di Suzuki Training Center Jakarta: Pelatihan dan Sertifikasi Level 2 Teknisi Roda 4 Suzuki di Suzuki Training Center Jakarta - Andre, Muhammad (Politeknik Piksi Ganesha Indonesia, 2026)
This community service activity aims to enhance the skills of Level 2 Suzuki four-wheeled vehicle technicians in analysing faults in Suzuki four-wheeled vehicles, with a focus on the chassis and engine. The programme was delivered using a Service Learning approach, employing hands-on demonstrations and assessed through practical evaluations or assessments of training material mastery using assessment tools designed in accordance with minimum training competency standards. The results of the programme indicate that the technicians achieved the minimum competency standards set. It can therefore be concluded that the objectives of this training were successfully achieved.